Turbidite emplacement on the southern Balearic Abyssal Plain (western Mediterranean Sea) during Marine Isotope Stages 1-3: An application of ITRAX XRF scanning of sediment cores to lithostratigraphic analysis - Rothwell, R; Hoogakker, B; Thomson, J; Croudace, I; Frenz, M (2006)
The upper part (0-20m) of along piston core from the SE Balearic Abyssal Plain - spanning the past 50 ka - has been studied using the ITRAX micro-XRF core scanner to obtain downcore elemental profiles. The Ca/Fe ratio was found to be an effective parameter to distinguish between turbidites and pelagites, because turbidites generally have higher Fe contents and lower Ca contents compared with pelagic intervals. Beds that were obscure when visually logged could be identified as turbidites or pelagites on their geochemical characteristics, allowing more complete subdivision of the sequence into genetic units. The ITRAX XRF data also provide useful information on textural grading, bioturbative mixing, identification of geochemically distinctive marker beds, indications of differences in provenance, and confirm or query the presence of early arrivals during turbidite emplacement. A chronostratigraphic framework for the core based on accelerator mass spectrometry (AMS) radiocarbon dating and correlation with oxygen isotope stages of pelagic intervals in other cores (using calcium carbonate stratigraphy) was also established. This shows that turbidite emplacement on this part of the Balearic Abyssal Plain has been modulated strongly by climate and sea-level change, with turbidite emplacement most frequent during the early Holocene when the rate of post-glacial sea-level rise was greatest. Deposition of the coarsest (i.e. sand and silt-based) turbidites at the core site was restricted to the full and Late Glacial (11-25 ka). Turbidite emplacement during Oxygen Isotope Stage 3 was rare. Most of the turbidites at the site are distal, but some coarse-grained-based turbidites are characterized by higher Sr/Ca ratios (possibly indicating a higher aragonite content), higher Ca and lower Fe contents compared to other turbidites, and are interpreted as having a more proximal shelf source. Such turbidites are generally rare, however, and restricted to full Glacial and Younger Dryas time. There is little evidence for large-scale seismogenic turbidites (expected to be seen as randomly timed emplacement, seemingly independent of eustatic control) at the core site, despite proximity to the seismically active Algerian margin 100 km to the south. This suggests that seismogenic turbidites must largely bypass this part of the plain. Although the ITRAX core scanner provides a rapid and non-destructive means of characterizing downcore geochemical distributions in great detail, interpretation of the data requires caution and assessment from an informed standpoint. Analytical artefacts such as those caused by water or organic content, degree of compaction, grain-size and mineral effects, unevenness of the cut core surface and poor discrimination of closely spaced element XRF peaks need identification and elimination. © The Geological Society of London 2006.